Quantitative assessment of specific carbonic anhydrase inhibitors effect on hypoxic cells using electrical impedance assays - Luciana Stanica; Mihaela Gheorghiu; Miruna Stan; Cristina Polonschii; Sorin David; Dumitru Bratu; Anca Dinischiotu; Claudiu T. Supuran; Eugen Gheorghiu (Taylor & Francis Group, 2017)
Carbonic anhydrase IX (CA IX) is an important orchestrator of hypoxic tumour environment, associated with tumour progression, high incidence of metastasis and poor response to therapy. Due to its tumour specificity and involvement in associated pathological processes: tumourigenesis, angiogenesis, inhibiting CA IX enzymatic activity has become a valid therapeutic option. Dynamic cell-based biosensing platforms can complement cell-free and end-point analyses and supports the process of design and selection of potent and selective inhibitors. In this context, we assess the effectiveness of recently emerged CA IX inhibitors (sulphonamides and sulphocoumarins) and their antitumour potential using an electrical impedance spectroscopy biosensing platform. The analysis allows discriminating between the inhibitory capacities of the compounds and their inhibition mechanisms. Microscopy and biochemical assays complemented the analysis and validated impedance findings establishing a powerful biosensing tool for the evaluation of carbonic anhydrase inhibitors potency, effective for the screening and design of anticancer pharmacological agents.